Management of major bleeds in patients with immune thrombocytopenia. (6th May 2020) - Mithoowani, Siraj; Cervi, Andrea; Shah, Nishwa; Ejaz, Resham; Sirotich, Emily; Barty, Rebecca; Li, Na; Nazy, Ishac; Arnold, Donald M.
Abstract: Background: A standard approach to the recognition and management of major bleeding in immune thrombocytopenia (ITP) is lacking. Methods: Retrospective cohort study of ITP patients presenting to the emergency department (ED) with severe thrombocytopenia (platelet count <20 × 10 9 /L) and bleeding in four academic hospitals from 2008 to 2016. We defined a major ITP bleed as a bleed at a critical site or causing hemodynamic instability. Results: We identified 112 ITP patients (n = 141 visits) who presented to the ED with platelets <20 × 10 9 /L and bleeding. Twenty‐nine patients (26%) had 32 ED visits with major bleeds. Risk factors for major bleeds were older age (odds ratio [OR] 1.03, 95% confidence interval [CI] 1.01‐1.06), male sex (OR 3.25, 95% CI 1.22‐9.32), and more prior ITP therapies (OR 1.42, 95% CI 1.10‐1.87). Acute treatment of major bleeds required a median of three treatments (interquartile range [IQR] 2‐4), which included intravenous immune globulin (91% of visits), corticosteroids (78% of visits), and platelet transfusions (75% of visits). Three patients (10%) died, nine (31%) developed recurrent bleeds, one (3%) developed arterial thrombosis, and one (3%) had permanent neurological disability. Six patients presented with minor bleeding and subsequently developed a major bleed after a median of 2 days (IQR 1‐3). All six patients had oral purpura and four of six had gross hematuria preceding the major bleed. Conclusions: Major ITP bleeds are associated with significant morbidity and mortality. Oral purpura and hematuria often preceded major bleeds. Further research is needed to refine the definition of a major ITP bleed and develop evidence‐based treatment strategies.